2019
DOI: 10.1051/meca/2020053
|View full text |Cite
|
Sign up to set email alerts
|

Milling diagnosis using artificial intelligence approaches

Abstract: The Industry 4.0 framework needs new intelligent approaches. Thus, the manufacturing industries more and more pay close attention to artificial intelligence (AI). For example, smart monitoring and diagnosis, real time evaluation and optimization of the whole production and raw materials management can be improved by using machine learning and big data tools. An accurate milling process implies a high quality of the obtained material surface (roughness, flatness). With the involvement of AI-based algorithms, mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Water footprints, pollution level, and global warming impact measuring are other challenges Industry 4.0 tends to deal with in this sector, while Canizares and Valero [ 19 ] found that the improvements of using IoT technologies in metal machining are very high resulting in the higher efficiency and cost reduction. Maier et al [ 20 ] and Knittel et al [ 21 ] have noticed similar benefits from digitization of the tools.…”
Section: Introductionmentioning
confidence: 81%
“…Water footprints, pollution level, and global warming impact measuring are other challenges Industry 4.0 tends to deal with in this sector, while Canizares and Valero [ 19 ] found that the improvements of using IoT technologies in metal machining are very high resulting in the higher efficiency and cost reduction. Maier et al [ 20 ] and Knittel et al [ 21 ] have noticed similar benefits from digitization of the tools.…”
Section: Introductionmentioning
confidence: 81%
“…Glatt et al [80] predicted the martensite content after cryogenic turning, considering the passive, cutting and feed forces and temperature, applying the PCC approach for feature selection and obtaining a RMSE of~0.8. Linear kernel was also applied for flatness classification prediction in honeycomb cores using the time-domain and frequency-domain (based on FFT) features of the force signal and the PCA for feature reduction [81,82]. Finally, Nain et al [83] implemented a Gaussian Process with Polynomial Kernel to predict the SR peculiarities of WEDM.…”
Section: Qualitymentioning
confidence: 99%
“…Also, several leading scientific journals are specifically dedicated to this research field involving many researchers and engineers from different disciplines: general computing, computer networks and IoT (Internet of Things), advanced statistics, signal processing, Artificial Intelligence, data science and data mining, intensive computing, embedded systems, etc.. Some diagnostic approaches are specifically designed or adapted for application fields and sectors such as manufacturing and production systems [3], industry 4.0 [4], material/tools interaction in milling [5] [6] [7], aeronautic sector [8], energy [9] [ 10], health [11], mobility/transport [12], waste management/wastewater treatment plants [13], rotating machines [14], … Predictive diagnostics and maintenance approaches are traditionally based on different methods:…”
Section: Introductionmentioning
confidence: 99%